Comparison of ultrasonographically measured fetal interventricular septal thickness between diabetic and healthy mother - Yesmina Rahman; A. S. Mohiuddin; Sadia Sultana; Nusrat Zahan; Fatema Tuj Johora (International Journal of Research in Medical Sciences, 2023)
Background: During pregnancy, metabolic changes occur in response to increased nutrient needs of the fetus and mother, including progressive insulin resistance that can lead to gestational diabetes mellitus (GDM). GDM can result in fetal complications. This study aimed to compare fetal interventricular septal thickness, measured by ultrasound, between diabetic and healthy mothers. Methods: This cross-sectional study was conducted at the department of radiology and imaging, BIRDEM, Dhaka, Bangladesh. A total of 334 subjects were enrolled in this study as per inclusion criteria. The study duration was 2 years; from July 2012 to June 2014. All study subjects were divided into 3 groups named group A, group B, and group C. 167 non-diabetic, 84 controlled diabetics, and 83 uncontrolled diabetic mothers were considered as group A, group B, and group C respectively. Data were analyzed by SPSS computed program. Results: In this study, 47.9% of subjects in group A were ≤25 years old, while 52.4% of group B and 53.0% of group C were in the 26-30 age range. The mean age was 25.9±3 years in group A, 25.5±2.9 years in group B, and 25.2+3.3 years in group C, with no statistically significant difference between the three groups (p>0.05). The mean gestational age was similar across the three groups, with no statistically significant difference (p>0.05). However, the mean fetal interventricular septal thickness was significantly different between the groups, with group A and B having similar thicknesses, while group C had a significantly larger thickness (p<0.05). The difference in fetal interventricular septal thickness was also statistically significant between the three groups at 32 weeks of gestational age (p<0.05). Conclusions: In this study, the fetal interventricular septal thickness was significantly higher in uncontrolled diabetic mothers followed by controlled diabetic and non-diabetic and almost alike between non-diabetic and controlled diabetic mothers. The study also revealed that M-mode ultra-sonogram measurement of interventricular septal thickness can be included in routine scanning during the third trimester.